Implementasi Kebijakan pada Program Magang dan Studi Independen Bersertifikat di Indonesia - Abdul Rahman; Daya Cipta Sukmajati; Mawar Mawar; Evi Satispi; Djoni Gunanto (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2023)
This research aims to analyze the policy implementation of independent campus on the certified internship and independent study (MSIB) program in Indonesia, as well as examine the supporting and inhibiting factors. The method uses two mixed approaches, qualitative and quantitative. Meanwhile, the theory used is Van Meter & Van Horn model. The results of this study found that policy implementation of MSIB program in Indonesia relatively good in aspects of program objectives, economic, social, and political conditions, also the characteristics of implementing agencies. Meanwhile, other aspects such as standards, resources, communication enforcement activities inter-organizational, and the disposition of the implementers still need to be improved. The supporting factors in the policy implementation of an independent campus on the MSIB program in Indonesia among others: 1) Relevance of learning in the MSIB program in the industrial world; 2) Clarity of cost components; 3) Adequate support from the C level and the President of Indonesia. Meanwhile, the inhibiting factors among others: 1) There is no standardization of credit conversion; 2) Lack responsiveness of mentors; 3) Delay in disbursement of stipend; 4) Weak helpdesk accessibility; 5) Disparity of funding components; and 6) Support from Campus entities for programs that not yet optimal.